Sex differences in 1‐year clinical outcomes after percutaneous coronary intervention with COMBO stents: From the COMBO collaboration. Issue 5 (21st March 2020) - Chandrasekhar, Jaya; Kerkmeijer, Laura S.; Kalkman, Deborah N.; Sartori, Samantha; Aquino, Melissa B.; Woudstra, Pier; Beijk, Marcel A.; Tijssen, Jan G.; Koch, Karel T.; Hájek, Petr; Atzev, Borislav; Hudec, Martin; et al.
Abstract: Background: The COMBO drug eluting stent is a novel device with luminal endothelial progenitor cell capture technology for rapid homogeneous endothelialization. Methods and results: We examined for sex differences in 1‐year outcomes after COMBO stenting from the COMBO collaboration, a pooled patient‐level dataset from the MASCOT and REMEDEE multicenter registries. The primary endpoint was 1‐year target lesion failure (TLF), composite of cardiac death, target vessel‐myocardial infarction (TV‐MI), or clinically driven target lesion revascularization (CD‐TLR). Secondary outcomes included stent thrombosis (ST). Adjusted outcomes were assessed using Cox regression methods. The study included 861 (23.8%) women and 2, 753 (76.2%) men. Women were older with higher prevalence of several comorbidities including diabetes mellitus. Risk of 1‐year TLF was similar in both sexes (3.8% vs. 3.9%, HR 0.92, 95% CI 0.59–1.42, p = .70), without sex differences in the incidence of cardiac death (1.6% vs. 1.5%, p = .78), TV‐MI (1.5% vs. 1.1%, p = .32), or CD‐TLR (2.0% vs. 2.2%, p = .67). Definite or probable ST occurred in 0.4% women and 1.0% men (HR 0.26, 95% CI 0.06–1.11, p = .069). Conclusions: Despite greater clinical risks at baseline, women treated with COMBO stents had similarly low 1‐year TLF and other ischemic outcomes compared to men.